Deep end - Asher, Jane 1946-; Moulder-Brown, John 1953-; Dors, Diana 1931-1984 (British Film Institute, 2011)
"Newly employed at a run-down London swimming baths, Mike (John Moulder-Brown) obsesses after his sassy and self-assured co-worker (Jane Asher) whilst collecting tips for the 'special services' he is expected to perform for clients (including the superb Diana Dors). Darkly comic and utterly compelling, this portrait of Britain in an era of uncertainty makes its long overdue return to the screen in a new digital restoration with extensive bonus features."
Original: Germany, UK 1970
Bildformat 1.85:1
Verlagsnummer BFIB1063
Special features: Presented in both High Definition and Standard Definition ; Starting Out: The Making of Jerzy Skolimowski's Deep End (2011, 74 min): a comprehensive new feature-length documentary ; Deep End: The Deleted Scenes (2011, 12 min): short documentary exploring the scenes that never made the grade ; Original theatrical trailer ; Careless Love (Francine Winham, 1976, 10 min): rare and disturbing tale in which a woman (Jane Asher) takes drastic action to keep the affections of the man she loves ; illustrated booklet featuring new essays by David Thompson, Yvonne Tasker, and Skolimowski expert Ewa Mazierska
Keywords: Film; DVD-Video; Blu-Ray-Disc